x + 6y = 2 4x - 3y = 10 Pick the first step to solving this system of equations using the addition method.

Add the equation first to get: 5x + 3y = 12 and then solve for x.

Add -6y to both sides of the equation to isolate the x variable in the top equation.

Multiply the top equation by 4 thus eliminating the x variable when the equations are added together.

Multiply the bottom equation by 2 thus eliminating the y variable when the equations are added together.

Respuesta :

x + 6y = 2
4x - 3y = 10

The first thing to do when solving a system of equations using the addition/elimination method is to multiply one or both of the equation by a value that will cancel out one of the variable terms. 

Based on this, the correct answer is D - multiply the bottom equation by 2 thus eliminating the y variable when the equations are added together:

x + 6y = 2                     x + 6y = 2
2(4x - 3y = 10)    -->    8x - 6y = 20

Hope this helps.

The value of [tex]x = \frac{11}{3}[/tex] and [tex]y = \frac{-2}{27}[/tex].

The required equation is 4x = 10 + 3y.

The required value of y is [tex]y = \frac{6}{7}[/tex]

The required value of x is [tex]x = \frac{22}{9}[/tex]

Given that,

Equation are x + 6y = 2,  4x - 3y = 10

We have to find,

Solving this system of equations using the addition method.

According to the question,

  • Add the equation first to get: 5x + 3y = 12 and then solve for x.

Then, x + 6y = 2, and 5x + 3y = 12

x + 6y = 2

x = 2 - 6y

Putting the value of x in the 2nd

5(2 - 6y) + 3y = 12

10 - 30y + 3y = 12

10 - 27y = 12

-27y = 12-10

-27y = 2

y = [tex]\frac{-2}{27}[/tex]

And the value of x.

[tex]x + 6y = 2\\x + 6(\frac{-2}{27}) = 2\\x + \frac{-12}{27} = 2\\27x - 12 = 54 \\27x = 66\\x = \frac{66}{27}\\x = \frac{11}{3}[/tex]

The value of [tex]x = \frac{11}{3}[/tex] and [tex]y = \frac{-2}{27}[/tex].

  • Add -6y to both sides of the equation to isolate the x variable in the top equation.

x + 6y = 2,  4x - 3y = 10

Subtract -6y from both equation,

Then x + 6y - 6y = 2 - 6y

x = 2 - 6y

And   4x - 3y - 6y = 10 - 6y

4x - 9y = 10 - 6y

The required equation is 4x = 10 + 3y

  • Multiply the top equation by 4 thus eliminating the x variable when the equations are added together.

4 ( x + 6y) = 4.2,

4x + 24y = 8

Adding equation 1 and 2 eliminate x

4x + 24y = 8

4x - 3y = 10

On adding the equation,

21y = 18

[tex]y = \frac{18}{21} \\y = \frac{6}{7}[/tex]

The required value of y is [tex]y = \frac{6}{7}[/tex]

  • Multiply the bottom equation by 2 thus eliminating the y variable when the equations are added together.

4x - 3y = 10

Multiply by 2

2( 4x - 3y) = 2.10

8x - 6y = 20

Adding the equation and eliminate y ,

8x - 6y = 20

x + 6y = 2

On adding

9x = 22

[tex]x = \frac{22}{9}[/tex]

The required value of x is [tex]x = \frac{22}{9}[/tex]

For more information about System of equation click the link given below.

https://brainly.com/question/24065247